“Um museu de grandes novidades”: : biopolítica, biopoder, colonialismo e necropolítica bolsonarista de 2018 à 2022. - Elíbio Junior, Antonio Manoel (2022)
This article aims to analyze the advance of the Bolsonarist extreme right in Brazil, taking into account the coup d'état suffered by Dilma Rousseff in 2016, when a series of social achievements that had advanced since 2003 were called into question. After attacks on the working class, such as Law 13467, known as labor reform, which largely curtailed workers' rights; and Constitutional Amendment 95, which limited public spending for 20 years, benefiting the business community and directly harming the quality of Brazilian public service; the path to the far right was being paved. Two years later, the election of Jair Bolsonaro marked the beginning of a period of strong attacks on freedoms, typical of a fascist government project.